CHRONOTYPE IN BREAST CANCER AND RELATION TO DESYNCHRONIZATION OF THE CIRCADIAN CYCLE - Gebin, Natália Gomes; Manoel, Wilmar José; Abreu, Deidimar Cássia Batista; Ataides, Fábio Silvestre; Vilanova-Costa, Cesar Augusto Sam Tiago; Leão-Cordeiro, Jacqueline Andréia Bernardes; Silva, Antonio Márcio Teodoro Cordeiro (Mastology, 2018)
Introduction: The circadian cycle plays several roles at the organism functions and are important to the maintenance of health, when synchronized. Nowadays, one of the main risk factors for the change of the sleep-wake cycle in the population is the high exposure to light at night, consequently deregulating the circadian cycle, inhibiting the release of melatonin and favoring oncogenesis. Objectives: The aim of this study was to identify the possible associations between circadian rhythm’s desynchronization and breast cancer. Methods: This is a descriptive cross-sectional study and two collection instruments were used in it: sociodemographic questionnaire and the Horne and Ostberg matutinal-vespertine questionnaire. They were applied in a group of 74 women in a highly complex oncology service. Results: To evaluate whether the discriminant factors such as night work and chronotype exerted some influence on the discriminated factor that is breast cancer, χ2 test was applied showing that the characteristics among the groups were similar and so it was not possible to confirm that there is a relationship between them. Conclusions: More studies about the subject is needed.